Measurement of ground motion near piles during driving - Woods, Richard; Athanasopoulos-Zekkos, Adda; Gkrizi, Athena; Pietrangelo, Anthony; Zimmerman, Andrew (American Society of Civil Engineers, 2014)
Two types of vibration damage caused by driving piles have been reported in the literature: direct structural damage and damage due to settlement. Direct damage results from vibratory excitation of structures at amplitude exceeding the structural tolerance. Damage from settlement is a consequence from vibratory densification of loose soils resulting in total or differential settlement of structures. Problems of settlement due to pile driving have been experienced recently by the Michigan Department of Transportation (MDOT) during operations associated with replacement of deteriorating bridges. The work described here represents an attempt to understand the mechanisms of energy transfer from steel H-piles driven with diesel hammers to the surrounding soil and the energy attenuation through the soil by measuring ground motion in the near vicinity of the pile. The main feature of this study consisted of installing motion transducers very close, within 0.5 foot, to piles and measuring the resulting ground motion during pile driving. Selection, fabrication, and installation of the transducers and preliminary measured pile driving vibrations are presented.